1986
DOI: 10.1007/bf02537243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary linolenate on the fatty acid composition of brain lipids in rats

Abstract: Weanling male rats were fed hydrogenated coconut oil to induce essential fatty acid (EFA) deficiency. After 15 weeks, the rats were divided into six groups. Five groups were fed graded amounts of purified linolenate (18:3 omega 3) with a constant amount of linoleate (18:2 omega 6) for six weeks. Fatty acid composition was determined in brain lipids. Increasing dietary 18:3 omega 3 resulted in a decrease in arachidonic acid (20:4 omega 6), docosatetraenoic acid (22:4 omega 6) and docosapentaenoic acid (22:5 ome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 19 publications
4
15
1
Order By: Relevance
“…The higher percentage of arachidonic acid in the membranes of group I (ratio 120) gave a reciprocal concentration of 18:2. A similar relationship was also observed with respect to the 22:6/18:3 ratio in the synaptosomal membranes from group III (ratio 8) [26,27]. These results can be explained on the basis of substrate concentrations and their availability for z desaturase enzyme [9].…”
Section: Discussionsupporting
confidence: 64%
“…The higher percentage of arachidonic acid in the membranes of group I (ratio 120) gave a reciprocal concentration of 18:2. A similar relationship was also observed with respect to the 22:6/18:3 ratio in the synaptosomal membranes from group III (ratio 8) [26,27]. These results can be explained on the basis of substrate concentrations and their availability for z desaturase enzyme [9].…”
Section: Discussionsupporting
confidence: 64%
“…Mice fed 10% fish oil (15) showed a transient rise in brain EPA, which mostly disappeared by 10 d of feeding. Some studies involving the feeding of large amounts of 18:3n-3 also showed little effect on brain EPA levels (42,43). In the present study, modest amounts (0.44% of calories) of 18:3, EPA, and DHA were fed to n-3 fatty acid-deficient chicks, and generally no more than trace amounts of EPA appeared in the brain and retina.…”
mentioning
confidence: 99%
“…These studies measured the accretion of the DHA in the total lipid and phospholipid of whole brain Anding and Hwang, 1986;Arbuckle et al, 1991), total lipid of the brain subcellular fractions (Bourre et al, 1984(Bourre et al, , 1989aYouyou et al, 1986) or individual phospholipids of whole brain (Foote et al, 1990;Galli et al, 1971;Samulski and Walker, 1982;Arbuckle et al, 1991). The present study focused on the influences of maternal dietary fish oil on (n-3) fatty acid deposit in individual phospholipids (i.e., PE, PI, PS, and PC) among different brain subcellular fractions, including Mt, Ms, Sy, and My of offspring.…”
Section: Discussionmentioning
confidence: 99%